Factors Affecting Late Infertility Examination - Budihastuti, Uki Retno; Melinawati, Eriana; Sari, Arum Dessy Rahma; Jatiningtyas, Abida Zuhra (Journal of Maternal and Child Health, 2020)
Background:  Infertility is the inability of a couple to get pregnant after 12 months of regular sexual intercourse at least 2-3 times a week without using contraception. Delay in the examination will have a bad impact considering that increasing age will affect the success of the handling of infertility, especially in women so it is necessary to know the factors that influence the delay of the initial examination in order to be overcome. This study aims to determine the factors that influence the late infertility examination.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted at Sekar Polyclinic, Dr. Moewardi Hospital, Surakarta, Central Java, from June to August 2019. A sample of 90 outpatients was selected by purposive sampling. The dependent variable was late infertility examination. The independent variables were family support, knowledge, accessibility, and education. The data was collected by medical record and questionnaire. The data were analyzed by a multiple logistic regression.Results: Late infertility examination decreased with strong family support (OR= 0.20; 95% CI= 0.06 to 0.62; p= 0.006), high knowledge (OR= 0.29; 95% CI= 0.09 to 0.92; p= 0.036), good accessibility (OR= 0.18; 95% CI= 0.05 to 0.59; p= 0.005), and high education (OR= 3.41; 95% CI= 0.95 to 12.17; p= 0.059).Conclusion: Late infertility examination decreases with strong family support, high knowledge, good accessibility, and high education.Keywords: infertility examination, family support, accessibility, knowledgeCorrespondence: Uki Retno Budihastuti. Department of Obstetrics and Gynecology, Dr. Moewardi Hospital,Jl. Kolonel Sutarto132, Jebres, Surakarta, Central Java. Email: ukiretno@gmail.com. Mobile: 08122656140.Journal of Maternal and Child Health (2020), 5(2): 206-212https://doi.org/10.26911/thejmch.2020.05.02.11